Immobilized Metal Complexes On Montmorillonite-K10 As Heterogeneous Catalyst For Epoxidation Of Cyclohexene - Nur Fatin Diana Binti Che Husin (Universiti Sains Islam Malaysian, 2024)
117 pages (including hard cover)